Nickel-zinc ferrite material as well as preparation method and application thereof
By regulating the main components and doping components of nickel-zinc ferrite materials, especially the introduction of Nd2O3 doping components, the problem of insufficient permeability and impedance of existing materials at high frequencies and high temperatures is solved, and the high performance improvement of the material is achieved and suitable for high-performance electronic devices.
Patent Information
- Application Number
- CN202510169510.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-02-17
AI Technical Summary
Existing nickel-zinc ferrite materials show insufficient magnetic permeability and impedance at high frequencies and high temperatures, and cannot meet the needs of high-performance electronic devices such as automotive supplies.
By regulating the composition and content of the main components and doping components in nickel-zinc ferrite materials, especially the introduction of Nd2O3 doping components, the material's magnetic permeability, saturated magnetic induction strength, Curie temperature and high-frequency impedance coefficient are optimized.
It realizes the high magnetic permeability, high saturation magnetic induction strength, high Curie temperature and high frequency and high impedance coefficient of nickel-zinc ferrite materials, which improves the comprehensive performance of the material and is suitable for high-performance electronic devices.
Smart Images

Figure BDA0005273496390000141 
Figure BDA0005273496390000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic materials, and in particular to a nickel-zinc ferrite material and a preparation method and application thereof. Background Art
[0002] With the development of electronic power technology, it is an inevitable trend for electronic devices to develop in the direction of miniaturization, high frequency and high current. Therefore, the performance requirements for soft magnetic materials in electronic devices are also increasing. NiZn soft ferrite has the advantages of excellent high frequency characteristics, good temperature stability, diverse formulas, large nonlinearity, simple preparation process, etc. It is widely used in television, communication, instrumentation, automatic control, electronic countermeasures and other fields.
[0003] NiZn ferrite materials can be divided into three categories according to their uses and characteristics: high frequency, high saturation magnetic induction intensity and high initial magnetic permeability. However, there are still inevitable disadvantages. For example, in order to make the high impedance NiZn ferrite material have a higher magnetic permeability, the ZnO content must be increased, which leads to a significant decrease in its Curie temperature. The high magnetic permeability will reduce its cutoff frequency, and the impedance drop is more obvious at a frequency of tens of megahertz.
[0004] Prior art CN115925405A discloses a high permeability and high Curie temperature NiCuZn soft magnetic ferrite material, wherein the main components include Fe2O3: 66.22wt% to 68.65wt%; ZnO: 18.30wt% to 22.15wt%; NiO: 7.75wt% to 9.85wt%; the balance is CuO; the doping components include Y2O3, MoO3, V2O5 and MnCO3, wherein Y2O3 accounts for 0.05wt% to 0.1wt% of the main component mass, MoO3 content accounts for 0.06wt% to 0.18wt% of the main component mass, V2O5 content accounts for 0.05wt% to 0.15wt% of the main component mass, and MnCO3 content accounts for 0.55wt% of the main component mass. At a test frequency of 100kHz, the initial permeability is 2011, and the specific loss coefficient is 28.78×10 -6 , Curie temperature is 145°C, saturation magnetic induction intensity Bs=352mT (10kHz, 4000A / m). The ferrite material disclosed in the prior art has extremely high initial magnetic permeability, but if it is needed to be used in vehicle-mounted products, its Curie temperature must reach above 160°C, but its Curie temperature is relatively low and cannot reach a higher level.
[0005] CN109320227 discloses a NiCuZn ferrite material and a preparation method and use thereof. The NiCuZn ferrite material is mainly composed of Fe2O3, ZnO, NiO and CuO. Taking the total molar amount of the NiCuZn ferrite material as 100%, the molar percentage of Fe2O3 is 48.8mol%-50mol%, the molar percentage of ZnO is 32-34mol%, the molar percentage of NiO is 6.5-8mol%, and the molar percentage of CuO is 8.5-12.7mol%. The prepared NiCuZn ferrite material has an initial magnetic permeability of 1600-2000 in the range of 100-300kHz, a saturation magnetic induction intensity Bs≥240mT at 25°C, and a Curie temperature of 95-110°C. The ferrite material disclosed in the prior art also has a relatively high initial magnetic permeability, but its saturation magnetic induction intensity is relatively low, and it is not suitable for common mode circuits. In addition, the Curie temperature is only 110°C, and the applicable field is relatively small.
[0006] Therefore, how to provide a nickel-zinc ferrite material having high magnetic permeability, saturation magnetic induction intensity, Curie temperature, and impedance coefficient has become a problem that needs to be solved urgently. Summary of the invention
[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a nickel-zinc ferrite material and a preparation method and application thereof. The present invention regulates the composition and content of the main components and doping components in the nickel-zinc ferrite material, while ensuring that it has a high magnetic permeability and saturation magnetic induction intensity, and also effectively improves the Curie temperature and high-frequency impedance coefficient of the nickel-zinc ferrite material.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a nickel-zinc ferrite material, the nickel-zinc ferrite material comprising a main component and a doping component, the main component comprising Fe2O3, NiO, ZnO and CuO, the doping component comprising Nd2O3, and the doping component accounts for 0.001-0.005wt% of the main component;
[0010] Taking the total mass of the main components as 100wt%, the content of Fe2O3 is 64.32-66.12wt%, the content of NiO is 8.89-9.91wt%, the content of ZnO is 17.12-18.15wt%, and the content of CuO is 6-10wt%.
[0011] In the present invention, the doping component accounts for "0.001-0.005wt%" of the main component, such as 0.001wt%, 0.0015wt%, 0.002wt%, 0.0025wt%, 0.003wt%, 0.0035wt%, 0.004wt%, 0.0045wt% or 0.005wt%; the selection range of Fe2O3 is "64.32-66.12wt%, such as %, 64.32wt%, 64.40wt%, 64.60wt%, 64.80wt%, 65.00wt%, 65.20wt%, 65.40wt%, 65.60wt%, 65.80wt%, 66.00wt% or 66.12wt%, etc.; the selection range of NiO is "8.89-9.91wt%, for example 8.89wt%, 8.90wt%, 9.00wt%, 9.10 wt%, 9.20wt%, 9.30wt%, 9.40wt%, 9.50wt%, 9.60wt%, 9.70wt%, 9.80wt%, 9.90wt% or 9.91wt%, etc.; the selection range of ZnO is "17.12-18.15wt%, for example, 17.12wt%, 17.20wt%, 17.30wt%, 17.40wt%, 17.50wt%, 17.6 % , 8.4wt%, 8.8wt%, 9.2wt%, 9.6wt% or 10wt% etc.; the selection range of the CuO is "6-10wt%", for example 6wt%, 6.4wt%, 6.8wt%, 7.2wt%, 7.6wt%, 8wt%, 8.4wt%, 8.8wt%, 9.2wt%, 9.6wt% or 10wt% etc.
[0012] The present invention regulates the composition and content of the main components of the nickel-zinc ferrite material and introduces a specific content of Nd2O3 doping components, which can ensure the high magnetic permeability and saturation magnetic induction intensity of the nickel-zinc ferrite material, and can also effectively improve the Curie temperature and high-frequency impedance coefficient of the material, so that the nickel-zinc ferrite material has excellent comprehensive performance. Among them, the introduction of copper oxide into the nickel-zinc ferrite material is intended to promote the solid phase reaction during pre-sintering and sintering; the doping of Nd2O3 can affect the crystal field in the material, increase the superconversion effect between magnetic ions, and help to improve its Curie temperature.
[0013] Preferably, the doping component accounts for 0.003-0.004wt% of the main component, such as 0.003wt%, 0.0032wt%, 0.0034wt%, 0.0036wt%, 0.0038wt% or 0.004wt%.
[0014] The present invention further regulates the content of the doping component, which can further avoid a significant decrease in the magnetic permeability of the ferrite material, while increasing the high-frequency impedance coefficient and Curie temperature of the ferrite material.
[0015] Preferably, the density of the nickel-zinc ferrite material is 4.5-5.5 g / cm 3 , for example 4.5g / cm 3 , 4.6g / cm 3 , 4.7g / cm 3 , 4.8g / cm 3 , 4.9g / cm 3 , 5.0g / cm 3 , 5.1g / cm 3 , 5.2g / cm 3 , 5.3g / cm 3 , 5.4g / cm 3 or 5.5g / cm 3 wait.
[0016] Preferably, the magnetic permeability of the nickel-zinc ferrite material is 883.9-996.3 H / m, for example, 883.9 H / m, 890.0 H / m, 900.0 H / m, 910.0 H / m, 920.0 H / m, 930.0 H / m, 940.0 H / m, 950.0 H / m, 960.0 H / m, 970.0 H / m, 980.0 H / m, 990.0 H / m or 996.3 H / m, etc.
[0017] Preferably, the saturation magnetic induction intensity of the nickel-zinc ferrite material is 374.8-380.8 mT, for example, 374.8 mT, 375.0 mT, 375.5 mT, 376.0 mT, 376.5 mT, 377.0 mT, 377.5 mT, 378.0 mT, 378.5 mT, 379.0 mT, 379.5 mT, 380.0 mT, 380.5 mT or 380.8 mT, etc.
[0018] Preferably, the impedance coefficient of the nickel-zinc ferrite material at 30 MHz is 60.8-62.3, for example, 60.8, 61.0, 61.2, 61.4, 61.6, 61.8, 62.0, 62.2 or 62.3.
[0019] Preferably, the impedance coefficient of the nickel-zinc ferrite material at 50 MHz is 74.6-76.6, for example, 74.6, 74.8, 75.0, 75.2, 75.4, 75.6, 75.8, 76.0, 76.2, 76.4 or 76.6.
[0020] Preferably, the Curie temperature of the nickel-zinc ferrite material is 130-180°C, for example, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C or 180°C, etc., preferably 160-180°C.
[0021] In a second aspect, the present invention provides a method for preparing the nickel-zinc ferrite material according to the first aspect, the preparation method comprising the following steps:
[0022] (1) Fe2O3, NiO, ZnO and CuO are first mixed according to the formula amount, and then pre-fired to obtain a pre-fired mixture;
[0023] (2) The pre-fired mixture, the formulated amount of Nd2O3 and the binder are mixed for a second time, and the mixture is pressed and sintered to obtain the nickel-zinc ferrite material.
[0024] The present invention provides a method for preparing a nickel-zinc ferrite material with high Curie temperature and high impedance coefficient. By adjusting the formula amount of main components and the addition amount of doping components, and combining a mixing process, a pressing process and a sintering process, the obtained nickel-zinc ferrite material can be ensured to have high magnetic permeability, high saturation magnetic induction intensity, and high frequency and high impedance coefficient, while its Curie temperature is effectively improved. The manufacturing process is simple and is conducive to industrial production.
[0025] Preferably, the first mixing in step (2) is carried out by ball milling.
[0026] Preferably, the first mixing time in step (1) is 2-3 h, for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h.
[0027] Preferably, the rotation speed of the first mixing in step (1) is 300-500r / min, for example, 300r / min, 320r / min, 340r / min, 360r / min, 380r / min, 400r / min, 420r / min, 440r / min, 460r / min, 480r / min or 500r / min, etc.
[0028] Preferably, in step (1), the first mixing is followed by a first drying.
[0029] Preferably, the product after the first drying is further subjected to a first screening.
[0030] Preferably, the mesh size of the first sieving is 20-50 mesh, such as 20 mesh, 25 mesh, 30 mesh, 35 mesh, 40 mesh, 45 mesh or 50 mesh.
[0031] Preferably, the pre-firing temperature in step (1) is 800-850°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C.
[0032] Preferably, the heating rate of the pre-calcination in step (1) is 1-3°C / min, for example, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min.
[0033] Preferably, the pre-burning time in step (1) is 1-3 h, for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h.
[0034] Preferably, the specific process of the second mixing in step (2) includes: mixing the pre-burnt mixture with the Nd2O3, and then granulating the mixed product with a binder to obtain a mixture.
[0035] Preferably, the pre-burned mixture is further subjected to a second screening before the second mixing.
[0036] Preferably, the mesh size of the second sieving is 20-50 mesh, such as 20 mesh, 25 mesh, 30 mesh, 35 mesh, 40 mesh, 45 mesh or 50 mesh.
[0037] Preferably, in the second mixing of step (2), the pre-burnt mixture and the Nd2O3 are mixed by ball milling.
[0038] Preferably, in the second mixing of step (2), the mixing time of the pre-burnt mixture and the Nd2O3 is 2-3h, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, etc.
[0039] Preferably, in the second mixing of step (2), the mixing speed of the pre-burnt mixture and the Nd2O3 is 300-500r / min, for example, 300r / min, 320r / min, 340r / min, 360r / min, 380r / min, 400r / min, 420r / min, 440r / min, 460r / min, 480r / min or 500r / min, etc.
[0040] Preferably, the product obtained by mixing the pre-burnt mixture and the Nd2O3 is further subjected to a second drying.
[0041] Preferably, the product after the second drying is further subjected to a third screening.
[0042] Preferably, the mesh size of the third screening is 20-50 meshes.
[0043] Preferably, the particle size D50 of the product after the third screening is 1.0-1.2 μm, such as 1.0 μm, 1.1 μm or 1.2 μm.
[0044] Preferably, the particle size D99 of the product after the third screening is 9.0-12.0 μm, such as 9.0 μm, 10.0 μm, 11.0 μm or 12.0 μm.
[0045] Preferably, the binder comprises polyvinyl alcohol.
[0046] Preferably, the concentration of the binder is 70-90wt%, for example, 70wt%, 75wt%, 80wt%, 85wt% or 90wt%.
[0047] Preferably, the amount of the binder added is 5-13wt% of the total mass of the pre-fired mixture and the Nd2O3, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt% or 13wt%, etc.
[0048] Preferably, the pressure of the compression molding in step (2) is 5-10 MPa, for example, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa, 10 MPa, etc.
[0049] Preferably, the sintering temperature in step (2) is 1140-1180°C, such as 1140°C, 1150°C, 1160°C, 1170°C or 1180°C.
[0050] In the present invention, if the sintering temperature is too high, the sample will be over-burned, and the magnetic permeability and other properties will be reduced; if the sintering temperature is too low, the solid phase reaction will be incomplete, and the comprehensive properties of the obtained ferrite material will be reduced.
[0051] Preferably, the sintering time in step (2) is 2-3 h, for example, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h.
[0052] Preferably, the heating rate of the sintering in step (2) is 3-5°C / min, for example, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min.
[0053] Preferably, the sintering atmosphere in step (2) is an air atmosphere.
[0054] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0055] (1) ball milling Fe2O3, NiO, ZnO and CuO according to the formula amount at a speed of 300-500 r / min for 2-3 hours under the condition of ball milling media and grinding aids, and after the first drying, the first dried product is first screened with a 20-50 mesh screen to obtain a first mixture, and then the first mixture is pre-calcined from room temperature to 800-850° C. at a heating rate of 1-3° C. / min for 1-3 hours to obtain a pre-calcined mixture;
[0056] (2) The pre-burned mixed material is screened for a second time using a 20-50 mesh screen, and then a formulated amount of Nd2O3 is added to the ball milling medium and the grinding aid, and the ball milling is performed at a speed of 300-500 r / min for 2-3 hours. After the second drying, the product after the second drying is screened for a third time using a 20-50 mesh screen, and the particle size D50 of the product after the third screening is 1.0-1.2 μm, and the particle size D99 is 9.0-12.0 μm. A binder with a concentration of 70-90wt% is added for stirring and granulation, wherein the amount of the binder added is 5-13wt% of the total mass of the pre-sintered mixture and the Nd2O3 to obtain a second mixture, and the second mixture is placed under a pressure of 5-10MPa for compression molding, and then, in an air atmosphere, the temperature is increased from room temperature to 1140-1180°C at a heating rate of 3-5°C / min, and the compressed product is sintered for 2-3h to obtain the nickel-zinc ferrite material.
[0057] In the present invention, the room temperature refers to a temperature of 20-30°C, such as 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C.
[0058] In a third aspect, the present invention provides an application of the nickel-zinc ferrite material according to the first aspect, wherein the nickel-zinc ferrite material is applied in the fields of television, communication, instrumentation, automatic control or electronic countermeasures.
[0059] Compared with the prior art, the present invention has at least the following beneficial effects:
[0060] (1) The present invention regulates the composition and content of the main components of the nickel-zinc ferrite material and introduces a specific content of Nd2O3 doping component, thereby ensuring that the nickel-zinc ferrite material has a high magnetic permeability and saturation magnetic induction intensity, and can also effectively improve the Curie temperature and high-frequency impedance coefficient of the material, thereby making the nickel-zinc ferrite material have excellent comprehensive performance.
[0061] (2) The present invention provides a method for preparing a nickel-zinc ferrite material with a high Curie temperature and a high impedance coefficient. By adjusting the formula amount of the main components and the amount of the doping components added, combined with a mixing process, a pressing process and a sintering process, it is possible to ensure that the nickel-zinc ferrite material has high magnetic permeability, high saturation magnetic induction intensity, and a high frequency and high impedance coefficient, while effectively improving its Curie temperature. The manufacturing process is simple and is conducive to industrial production. DETAILED DESCRIPTION
[0062] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0063] Example 1
[0064] The present embodiment provides a nickel-zinc ferrite material, including a main component and a doping component. The total mass of the main component is 100wt%, the main component includes 64.5wt% of Fe2O3, 9wt% of NiO, 17.5wt% of ZnO, and 9wt% of CuO. The doping component includes Nd2O3, and Nd2O3 accounts for 0.004wt% of the total mass of the main component. The density of the nickel-zinc ferrite material is about 5.1g / cm 3 .
[0065] This embodiment also provides a method for preparing the nickel-zinc ferrite material, and the specific steps include the following contents:
[0066] (1) According to the formula amount, Fe2O3, NiO, ZnO and CuO are ball-milled at a speed of 390 r / min for 2.5 h with water as a grinding aid and zirconia balls as ball-milling media. After a first drying, the product after the first drying is screened with a 30-mesh sieve to obtain a first mixture. Then, the first mixture is heated from a room temperature of 25°C to 820°C at a heating rate of 2°C / min and pre-fired for 2 h to obtain a pre-fired mixture.
[0067] (2) The pre-sintered mixture obtained in step (1) is screened for a second time using a 30-mesh sieve, and then a formulated amount of Nd2O3 is added. Under the condition of using water as a grinding aid and zirconium oxide balls as ball milling media, the mixture is ball milled at a speed of 390 r / min for 2.5 h. After a second drying, the product after the second drying is screened for a third time using a 30-mesh sieve, wherein the particle size D50 of the product after the third screening is 1.0-1.2 μm, and the particle size D90 of the second mixture is 9.0-12.0 μm. PVA glue with a concentration of 80wt% is added to the product for stirring and granulation, and the amount of PVA glue added is 10wt% of the total mass of the pre-sintered mixture and Nd2O3 to obtain a second mixture. The second mixture is then placed under a pressure of 6MPa and pressed into a sample ring with an inner diameter of 10mm, an outer diameter of 20mm, and a height of 5mm. Then, the obtained sample ring is heated from room temperature of 25°C to 1150°C at a heating rate of 3°C / min in an air atmosphere and sintered for 2h to obtain a nickel-zinc ferrite material.
[0068] Example 2
[0069] The present embodiment provides a nickel-zinc ferrite material, including a main component and a doping component. The total mass of the main component is 100wt%, the main component includes 64.32wt% of Fe2O3, 9.91wt% of NiO, 17.12wt% of ZnO, and 8.65wt% of CuO. The doping component includes Nd2O3, and Nd2O3 accounts for 0.004wt% of the total mass of the main component. The density of the nickel-zinc ferrite material is 5.1g / cm 3 .
[0070] This embodiment also provides a method for preparing the nickel-zinc ferrite material, and the specific steps include the following contents:
[0071] (1) According to the formula, Fe2O3, NiO, ZnO and CuO are ball-milled at a speed of 300 r / min for 3 h with water as a grinding aid and zirconia balls as ball-milling media. After the first drying, the first dried product is sieved with a 30-mesh sieve to obtain a first mixture. Then, the first mixture is heated from room temperature of 25°C to 800°C at a heating rate of 3°C / min for pre-calcining for 3 h to obtain a pre-calcined mixture.
[0072] (2) The pre-sintered mixture obtained in step (1) is screened for a second time using a 30-mesh sieve, and then a formulated amount of Nd2O3 is added. Under the condition of using water as a grinding aid and zirconium oxide balls as ball milling media, the mixture is ball milled at a speed of 300 r / min for 3 hours. After a second drying, the product after the second drying is screened for a third time using a 30-mesh sieve, wherein the particle size D50 of the product after the third screening is 1.0-1.2 μm, and the particle size D90 of the second mixture is 9.0-12.0 μm. The product after the third screening is PVA glue with a concentration of 70wt% is added to the material for stirring and granulation, the amount of PVA glue added is 10wt% of the total mass of the pre-sintered mixture and Nd2O3, to obtain a second mixture, and then the second mixture is placed under a pressure of 5MPa for pressing into a sample ring, the inner diameter of the sample ring is 10mm, the outer diameter is 20mm, and the height is 5mm. Then, the obtained sample ring is heated from room temperature of 25°C to 1140°C at a heating rate of 3°C / min in an air atmosphere and sintered for 3h to obtain a nickel-zinc ferrite material.
[0073] Example 3
[0074] The present embodiment provides a nickel-zinc ferrite material, including a main component and a doping component. The total mass of the main component is 100wt%, the main component includes 66.12wt% of Fe2O3, 8.89wt% of NiO, 18.15wt% of ZnO, and 6.84wt% of CuO. The doping component includes Nd2O3, and Nd2O3 accounts for 0.004wt% of the total mass of the main component. The density of the nickel-zinc ferrite material is 5.1g / cm 3 .
[0075] This embodiment also provides a method for preparing the nickel-zinc ferrite material, and the specific steps include the following contents:
[0076] (1) According to the formula, Fe2O3, NiO, ZnO and CuO are ball-milled at a speed of 500 r / min for 2 h with water as a grinding aid and zirconium oxide balls as ball-milling media. After the first drying, the first dried product is screened with a 30-mesh sieve to obtain a first mixture. Then, the first mixture is heated from room temperature of 25°C to 850°C at a heating rate of 3°C / min and pre-fired for 1 h to obtain a pre-fired mixture.
[0077] (2) The pre-sintered mixture obtained in step (1) is screened for the second time using a 30-mesh sieve, and then a formulated amount of Nd2O3 is added, and water is used as a grinding aid and zirconium oxide balls are used as ball milling media, and the mixture is ball milled at a speed of 500 r / min for 2 h. After a second drying, the product after the second drying is screened for the third time using a 30-mesh sieve, and the particle size D50 of the product after the third screening is 1.0-1.2 μm, and the particle size D90 of the second mixture is 9.0-12.0 μm. The product after the third screening is PVA glue with a concentration of 90wt% is added to the mixture for stirring and granulation, wherein the amount of PVA glue added is 10wt% of the total mass of the pre-sintered mixture and Nd2O3 to obtain a second mixture, and then the second mixture is placed under a pressure of 10MPa and pressed into a sample ring with an inner diameter of 10mm, an outer diameter of 20mm, and a height of 5mm. Then, the obtained sample ring is heated from room temperature of 25°C to 1180°C at a heating rate of 5°C / min in an air atmosphere and sintered for 2h to obtain a nickel-zinc ferrite material.
[0078] Example 4
[0079] The difference between this embodiment and embodiment 1 is that in the nickel-zinc ferrite material provided in this embodiment, Nd2O3 accounts for 0.003wt% of the total mass of the main components. The rest of the contents are the same as those in embodiment 1.
[0080] Example 5
[0081] The difference between this embodiment and embodiment 1 is that in the nickel-zinc ferrite material provided in this embodiment, Nd2O3 accounts for 0.002 wt% of the total mass of the main components. The rest of the contents are the same as those in embodiment 1.
[0082] Example 6
[0083] The difference between this embodiment and embodiment 1 is that in the nickel-zinc ferrite material provided in this embodiment, Nd2O3 accounts for 0.001wt% of the total mass of the main components. The rest of the contents are the same as those in embodiment 1.
[0084] Example 7
[0085] The difference between this embodiment and embodiment 1 is that in the nickel-zinc ferrite material provided in this embodiment, Nd2O3 accounts for 0.005wt% of the total mass of the main components. The rest of the contents are the same as those in embodiment 1.
[0086] Comparative Example 1
[0087] The difference between this comparative example and Example 1 is that in the nickel-zinc ferrite material provided in this comparative example, Nd2O3 accounts for 0.01 wt% of the total mass of the main components. The rest of the contents are the same as those in Example 1.
[0088] Comparative Example 2
[0089] The difference between this comparative example and Example 1 is that Nd2O3 is omitted in the nickel-zinc ferrite material provided in this comparative example. The rest of the contents are the same as those in Example 1.
[0090] Comparative Example 3
[0091] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 66.89wt%, the content of NiO is 7.64wt%, the content of ZnO is 19.54wt%, and the content of CuO is 5.93wt%. The rest of the contents are the same as Example 1.
[0092] Comparative Example 4
[0093] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 67.05wt%, the content of NiO is 7.42wt%, the content of ZnO is 20.37wt%, and the content of CuO is 5.16wt%. The rest of the contents are the same as Example 1.
[0094] Comparative Example 5
[0095] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 63.76wt%, the content of NiO is 9.81wt%, the content of ZnO is 17.64wt%, and the content of CuO is 8.79wt%. The rest of the contents are the same as Example 1.
[0096] Comparative Example 6
[0097] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 67.12wt%, the content of NiO is 8.97wt%, the content of ZnO is 17.32wt%, and the content of CuO is 6.59wt%. The rest of the contents are the same as Example 1.
[0098] Comparative Example 7
[0099] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 65.94wt%, the content of NiO is 8.14wt%, the content of ZnO is 20.76wt%, and the content of CuO is 5.16wt%. The rest of the contents are the same as Example 1.
[0100] Comparative Example 8
[0101] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 65.24wt%, the content of NiO is 10.27wt%, the content of ZnO is 18.05wt%, and the content of CuO is 6.44wt%. The rest of the contents are the same as Example 1.
[0102] Comparative Example 9
[0103] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 64.81wt%, the content of NiO is 9.65wt%, the content of ZnO is 16.34wt%, and the content of CuO is 9.20wt%. The rest of the contents are the same as Example 1.
[0104] Comparative Example 10
[0105] The difference between this comparative example and Example 1 is that: in the nickel-zinc ferrite material provided in this comparative example, the total mass of the main components is 100wt%, the content of Fe2O3 is 64.73wt%, the content of NiO is 9.67wt%, the content of ZnO is 19.13wt%, and the content of CuO is 6.47wt%. The rest of the contents are the same as Example 1.
[0106] The nickel-zinc ferrite materials provided in Examples 1-7 and Comparative Examples 1-10 were tested for magnetic permeability, impedance, saturation magnetic induction intensity and Curie temperature, respectively.
[0107] (1) Magnetic permeability test: Agilent E4991A analyzer was used to test the real part of magnetic permeability μ' at 1 MHz.
[0108] (2) Impedance test: The impedance of the nickel-zinc ferrite material obtained by the Agilent E4991A analyzer is used to calculate the dimensionless impedance coefficient. The calculation formula is as follows:
[0109] Z / (A e / L e );
[0110] Among them, Z is impedance, Ae is the window area of ferrite material, and Le is the magnetic path length.
[0111] (3) Saturation magnetic induction intensity: The nickel-zinc ferrite material obtained in the embodiment and the comparative example was evenly wound with 35 turns of a straight 0.4 mm copper wire. The test conditions were 50 Hz, the test temperature was 25° C., and the maximum value of the applied magnetic field was 4000 A / m.
[0112] (4) Curie temperature: The nickel-zinc ferrite material obtained in the embodiment and the comparative example was evenly wound with 10 turns of a straight 0.4 mm copper wire and then placed in an oven with 30°C as the starting temperature point and 10°C as an interval. The magnetic permeability was measured using a Wenco 6500B. The point where the magnetic permeability becomes 0 is the Curie temperature Tc.
[0113] The test results of the above parameters are shown in Table 1:
[0114] Table 1
[0115]
[0116]
[0117] The test results show that:
[0118] (1) It can be seen from Examples 1 to 7 that the present invention, by regulating the composition and content of the main components and doping components in the nickel-zinc ferrite material, ensures that it has a high magnetic permeability and saturation magnetic induction intensity, while also effectively improving the Curie temperature and high-frequency impedance coefficient of the nickel-zinc ferrite material. Further, by regulating the doping amount of the doping component, the magnetic permeability, saturation magnetic induction intensity, high-frequency impedance coefficient, and Curie temperature of the nickel-zinc ferrite material can be further improved, thereby obtaining a nickel-zinc ferrite material with better comprehensive performance.
[0119] (2) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that if the amount of the doping component Nd2O3 added to the nickel-zinc ferrite provided by the present invention is too high, the magnetic permeability will decrease significantly. This is because Nd 3+ It will be localized between the grain boundaries, hindering the displacement of the magnetic domain wall; if the doping component Nd2O3 is missing, the Curie temperature of the material will become lower. This is because there is no Nd 3+ It will reduce the superexchange effect between magnetic ions.
[0120] (3) By comparing Example 1 with Comparative Examples 3-10, it can be seen that in the nickel-zinc ferrite material provided by the present invention, if the content of Fe2O3 is too low, the high-frequency impedance coefficient is too low, and if the content of Fe2O3 is too high, the magnetic permeability is too low; if the content of NiO is too low, the saturation magnetic induction intensity Bs is too low, and if the content of NiO is too high, the magnetic permeability decreases; if the content of ZnO is too low, the magnetic permeability is too low, and if the content of ZnO is too high, the comprehensive performance of the ferrite material decreases.
[0121] In summary, the present invention can ensure the high magnetic permeability and saturation magnetic induction intensity of the nickel-zinc ferrite material by regulating the composition and content of the main components of the nickel-zinc ferrite material and introducing a specific content of Nd2O3 doping components, while also effectively improving the Curie temperature and high-frequency impedance coefficient of the material, thereby making the nickel-zinc ferrite material have excellent comprehensive performance.
[0122] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A nickel-zinc ferrite material, characterized in that: The nickel-zinc ferrite material comprises a main component and a doping component, wherein the main component comprises Fe2O3, NiO, ZnO and CuO, and the doping component comprises Nd2O3, and the doping component accounts for 0.001-0.005wt% of the main component; Taking the total mass of the main components as 100wt%, the content of Fe2O3 is 64.32-66.12wt%, the content of NiO is 8.89-9.91wt%, the content of ZnO is 17.12-18.15wt%, and the content of CuO is 6-10wt%.
2. The nickel-zinc ferrite material according to claim 1, characterized in that: The doping component accounts for 0.003-0.004wt% of the main component; Preferably, the density of the nickel-zinc ferrite material is 4.5-5.5 g / cm 3 .
3. The nickel-zinc ferrite material according to claim 1 or 2, characterized in that: The magnetic permeability of the nickel-zinc ferrite material is 883.9-996.3 H / m; Preferably, the saturation magnetic induction intensity of the nickel-zinc ferrite material is 374.8-380.8 mT; Preferably, the impedance coefficient of the nickel-zinc ferrite material at 30 MHz is 60.8-62.3; Preferably, the impedance coefficient of the nickel-zinc ferrite material at 50 MHz is 74.6-76.6; Preferably, the Curie temperature of the nickel-zinc ferrite material is 130-180°C, preferably 160-180°C.
4. A method for preparing the nickel-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Fe2O3, NiO, ZnO and CuO are first mixed according to the formula amount, and then pre-fired to obtain a pre-fired mixture; (2) The pre-fired mixture, the formulated amount of Nd2O3 and the binder are mixed for a second time, and the mixture is pressed and sintered to obtain the nickel-zinc ferrite material.
5. The preparation method according to claim 4, characterized in that: Step (2) the first mixing is performed by ball milling; Preferably, the first mixing time in step (1) is 2-3 hours; Preferably, the rotation speed of the first mixing in step (1) is 300-500 r / min; Preferably, in step (1), the first mixing is followed by a first drying; Preferably, the first dried product is further subjected to a first screening; Preferably, the mesh size of the first sieving is 20-50 meshes.
6. The preparation method according to claim 4 or 5, characterized in that: The pre-burning temperature in step (1) is 800-850°C; Preferably, the heating rate of the pre-calcination in step (1) is 1-3°C / min; Preferably, the pre-burning time in step (1) is 1-3 hours.
7. The preparation method according to any one of claims 4 to 6, characterized in that: Step (2) The specific process of the second mixing includes: mixing the pre-burned mixed material with the Nd2O3, and then granulating the mixed product with a binder to obtain a mixture; Preferably, the pre-burned mixture is further subjected to a second screening before the second mixing; Preferably, the mesh size of the second sieving is 20-50 mesh; Preferably, in the second mixing of step (2), the pre-burned mixture and the Nd2O3 are mixed by ball milling; Preferably, in the second mixing of step (2), the mixing time of the pre-burned mixture and the Nd2O3 is 2-3h; Preferably, in the second mixing of step (2), the mixing speed of the pre-burned mixture and the Nd2O3 is 300-500 r / min; Preferably, the product after the pre-burned mixed material and the Nd2O3 are mixed is further subjected to a second drying; Preferably, the product after the second drying is further subjected to a third screening; Preferably, the mesh size of the third sieving is 20-50 mesh; Preferably, the particle size D50 of the product after the third sieving is 1.0-1.2 μm; Preferably, the particle size D99 of the product after the third sieving is 9-12 μm; Preferably, the binder comprises polyvinyl alcohol; Preferably, the concentration of the binder is 70-90wt%; Preferably, the added amount of the binder is 5-13wt% of the total mass of the pre-fired mixture and the Nd2O3.
8. The preparation method according to any one of claims 4 to 7, characterized in that: The pressure of the compression molding in step (2) is 5-10 MPa; Preferably, the sintering temperature in step (2) is 1140-1180°C; Preferably, the sintering time in step (2) is 2-3 hours; Preferably, the heating rate of the sintering in step (2) is 3-5°C / min; Preferably, the sintering atmosphere in step (2) is an air atmosphere.
9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: (1) ball milling Fe2O3, NiO, ZnO and CuO according to the formula amount at a speed of 300-500 r / min for 2-3 hours under the condition of ball milling media and grinding aids, and after the first drying, the first dried product is first screened with a 20-50 mesh screen to obtain a first mixture, and then the first mixture is pre-calcined from room temperature to 800-850° C. at a heating rate of 1-3° C. / min for 1-3 hours to obtain a pre-calcined mixture; (2) The pre-burned mixed material is screened for a second time using a 20-50 mesh screen, and then a formulated amount of Nd2O3 is added to the ball milling medium and the grinding aid, and the ball milling is performed at a speed of 300-500 r / min for 2-3 hours. After the second drying, the product after the second drying is screened for a third time using a 20-50 mesh screen, and the particle size D50 of the product after the third screening is 1.0-1.2 μm, and the particle size D99 is 9.0-12.0 μm. A binder with a concentration of 70-90wt% is added for stirring and granulation, wherein the amount of the binder added is 5-13wt% of the total mass of the pre-sintered mixture and the Nd2O3 to obtain a second mixture, and the second mixture is placed under a pressure of 5-10MPa for compression molding, and then, in an air atmosphere, the temperature is increased from room temperature to 1140-1180°C at a heating rate of 3-5°C / min, and the compressed product is sintered for 2-3h to obtain the nickel-zinc ferrite material.
10. An application of the nickel-zinc ferrite material according to any one of claims 1 to 3, characterized in that: The nickel-zinc ferrite material is used in the fields of television, communication, instrumentation, automatic control or electronic countermeasures.
Citation Information
Patent Citations
NiCuZn soft magnetic ferrite material with high magnetic conductivity and high Curie temperature and preparation method of NiCuZn soft magnetic ferrite material
CN115925405A
Magneto-plumbite type permanent magnetic ferrite and manufacturing method thereof
CN102010194A
Nickel-zinc soft ferrite for wireless charging and preparation method and application thereof
CN108164260A
Magnetic powder for magnetic recording medium and magnetic recording medium using the powder
JP1986131230A
Ferrite magnetic material and production method therefor
JP2003238239A